Effect of ultra-low temperature storage on the viability of pepper pollen and its implications for hybrid breeding - Du, Kanghua; Zhang, Da; Ma, Jixian; Dan, Zhong; Wen, Xianqin; Lv, Weiwu; Yang, Long; Bao, Lingfeng; Li, Yirong; Chen, Guangping; Zhang, Jie; Mu, Wanfu (Frontiers in Plant Science, 2025)
Pollen plays a vital role in plant reproduction, acting as a carrier of male genetic material for fertilization and ensuring species propagation and the maintenance of biodiversity. Ultra-low temperature preservation of pollen provides a reliable method for long-term storage while preserving its viability, thereby facilitating crop breeding, genetic resource conservation, and ecological restoration. This study aimed to establish a method for long-term preservation of pepper pollen under ultra-low temperature conditions. Pollen was collected from unopened flowers during the peak flowering stage of pepper plants and subjected to sequential treatments including pollen dispersal, drying, dehydration (water content of pollen < 10%), sealing with inert gas (nitrogen), pre-cooling treatment, long-term preservation at −80°C, thawing treatment followed by artificial pollination. The results demonstrated that pepper pollen preserved for one year using our method maintained a pollination rate over 90%. Comparisons with fresh pollen (CK) indicated no significant differences in either the number or quality of hybrid seeds. This study establishes a theoretical and practical foundation for crop genetic breeding and germplasm conservation research, thereby facilitating the rapid advancement of hybrid breeding in pepper.